Aplikasi Sistem Irigasi Tetes Berbasis Mikrokontroler Arduino dalam Budidaya Tanaman Pakcoy (Brassica rapa l.) - Rijuniansi Grishella Rishelbi Silitonga; Daniel Peter Mantilen Ludong; Meicsy Eldad Israel Najoan (Universitas Sam Ratulangi, 2023)
The purpose of this study was to examine the application of a drip irrigation system based on an Arduino microcontroller in the cultivation of pakcoy (Brassica rapa l.) and the development of pakcoy plant growth, which included plant height and mass/weight of pakcoy plants. The data or information gathered during the study was classified based on the research objectives, observed using experimental methods, and processed using quantitative descriptive analysis. In this study, the microcontroller has passed the testing stages, including soil moisture sensor V1.2, ultrasonic sensor, DHT11 sensor, and GY-49 lux light sensor, which are working well so they can be implemented. The application of the Arduino microcontroller-based drip irrigation system using a soil moisture sensor works to detect based on the determined soil moisture limit value, namely the 60% setting point limit. Plant growth using a drip irrigation system based on a microcontroller resulted in plant height with an average value of 19.60 cm/plant and a mass weight of pakcoy plant yielding a total average harvest of 48.2 g/plant.